2005
DOI: 10.1007/s11176-005-0421-9
|View full text |Cite
|
Sign up to set email alerts
|

Is Triphenylverdazyl an Indicator for Solvent-Separated Ion Pair?

Abstract: The hypothesis implying complete capture of solvent-separated ion pairs by triphenylverdazyls used as internal indicators for unimolecular heterolysis of organic compounds was critically analyzed. Products of heterolysis of diphenylmethyl bromide in anhydrous acetonitrile in the presence of triphenylverdazyl were identified, and their distribution was determined. Alkylation of verdazyl under kinetic conditions almost does not occur, and verdazyl is consumed as a result of its reaction with hydrogen bromide lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…123 The results obtained in a study of the S N reaction of benzhydryl bromide in anhydrous acetonitrile 124 showed that alkylation of (75) rarely occurs; rather, it reacts with HBr formed when traces of water in the solvent react with the alkyl halide or its carbenium ion. Other arguments against the hypothesis that triphenylverdazyl is a trapping agent for solvent-separated ion pairs are given.…”
Section: Miscellaneous Kinetic Studiesmentioning
confidence: 99%
“…123 The results obtained in a study of the S N reaction of benzhydryl bromide in anhydrous acetonitrile 124 showed that alkylation of (75) rarely occurs; rather, it reacts with HBr formed when traces of water in the solvent react with the alkyl halide or its carbenium ion. Other arguments against the hypothesis that triphenylverdazyl is a trapping agent for solvent-separated ion pairs are given.…”
Section: Miscellaneous Kinetic Studiesmentioning
confidence: 99%